Implementation of Virtual Reality Based Learning Media At Pesantren Elementary School - Wijayama, Bayu; Handoyo, Eko; Wahyudin, Agus; Ahmadi, Farid (Universitas Negeri Semarang, 2024)
This research aims to analyse the implementation of Virtual Reality (VR)-based learning media in public primary schools (SDN) to improve the effectiveness and engagement of students in the learning process. The problem raised in this research is the low engagement and motivation of students in conventional learning, which often results in a lack of understanding and academic achievement. This research used a qualitative approach with descriptive method. The research subjects consisted of 5th and 6th grade students, teachers, and principals at SDNs that have adopted VR-based learning media. Data collection techniques included observation, in-depth interviews, and documentation studies. Data validation was conducted using triangulation techniques to ensure the accuracy and reliability of the data obtained. The collected data were analyzed using interactive analysis method, which consists of data collection, data reduction, data presentation, and conclusion drawing stages. The results showed that the implementation of VR-based learning media was able to significantly increase student engagement and motivation. Students were more enthusiastic in attending lessons and showed improved understanding of the material, as well as improvement in cognitive ability and comprehension of subject matter, especially in science and history subjects. Constraints include the need for technical training for teachers and the limitations of VR devices. The implication of this research is the importance of developing and implementing technology-based learning media in primary schools to create a more interactive and engaging learning experience for students.